PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN PENALARAN SISWA PADA MATERI PELUANG DI SMA KELAS XII - Yusma Riza Zulaicha; Makbul Muksar; Adbur Rahman (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
This research is intended to develop a valid, practical, and effective mathematical learning device based on a scientific approach to improve students' reasoning on the opportunity material in class XII SMA. The development model used in this research is the Dick and Carey model. Learning tools developed in the form of lesson plans and worksheets. RPP and worksheets are prepared by referring to the scientific approach which contains 5M (observing, asking questions, gathering information, reasoning, communicating). The worksheets that are compiled also contain the steps of the Polya's model of reasoning, namely: 1) observation of a problem, 2) formulation of allegations of the problem, 3) generalization, and 4) verification of allegations using new problems. This research has produced learning tools that are valid, practical, and effective.